Effect of SI14 and GB21 Acupressure on Early Breast Milk Release in Postpartum Women: A Pre-Experimental Study - Zullliati Zullliati; Istiqomah Istiqomah; Nita Hestiyana (An Idea Health Journal, 2025)
Background: Optimizing breast milk production in the early postpartum period is critical, given significant discrepancies between national lactation targets and actual field coverage. Early Breastfeeding Initiation (IMD) within the first two hours after delivery is a key factor in long-term lactation success; however, postpartum stress frequently delays milk production and serves as a primary barrier. This study employed a quantitative, pre-experimental, posttest-only control group design. Acupressure at SI 14 and GB 21 points was administered to the intervention group during the fourth stage of labor, while the control group received standard care. The majority of participants were of reproductive age, with 70% aged within the typical reproductive range and 60% having higher parity. Statistical analysis revealed a significant difference in breast milk production between the intervention and control groups (p = 0.007, < 0.05). These findings indicate that acupressure at SI 14 and GB 21 points significantly enhances the initial release of breast milk in postpartum mothers during the fourth stage of labor.